2007
DOI: 10.1111/j.1574-6941.2006.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic approach for the isolation of a novel low-temperature-active lipase from uncultured bacteria of marine sediment

Abstract: A novel lipase was isolated from a metagenomic library of Baltic Sea sediment bacteria. Prokaryotic DNA was extracted and cloned into a copy control fosmid vector (pCC1FOS) generating a library of >7000 clones with inserts of 24-39 kb. Screening for clones expressing lipolytic activity based on the hydrolysis of tributyrin and p-nitrophenyl esters, identified 1% of the fosmids as positive. An insert of 29 kb was fragmented and subcloned. Subclones with lipolytic activity were sequenced and an open reading fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 61 publications
(123 reference statements)
4
92
0
3
Order By: Relevance
“…These include low substrate affinity, thermolability, and high specific activity at low temperatures, which can together help achieve saving in energy costs and in reducing undesirable chemical side reactions; as well as allowing rapid thermal inactivation (Cavicchioli et al, 2002;Santiago et al, 2016). Other "cold-active" lipolytic enzymes from family IV have previously been described, but these usually possess higher optimal temperatures (35-50 • C; Hårdeman and Sjöling, 2007;Fu et al, 2011), whereas our esterase has a high activity at 4-40 • C, identifying it as truly "cold-active." In addition this work also broadens the description of members of the lipolytic enzyme family IV, as thermophilic and mesophilic enzymes of this family have to date been already described (Rhee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These include low substrate affinity, thermolability, and high specific activity at low temperatures, which can together help achieve saving in energy costs and in reducing undesirable chemical side reactions; as well as allowing rapid thermal inactivation (Cavicchioli et al, 2002;Santiago et al, 2016). Other "cold-active" lipolytic enzymes from family IV have previously been described, but these usually possess higher optimal temperatures (35-50 • C; Hårdeman and Sjöling, 2007;Fu et al, 2011), whereas our esterase has a high activity at 4-40 • C, identifying it as truly "cold-active." In addition this work also broadens the description of members of the lipolytic enzyme family IV, as thermophilic and mesophilic enzymes of this family have to date been already described (Rhee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, several groups isolated novel enzymes from various environments (Ranjan et al, 2005;Rhee et al, 2005;Feng et al, 2007;Hardeman and Sjoling, 2007;Tirawongsaroj et al, 2008), and many of them were found to offer a good potential as new tools for industrial applications, because their biophysical properties arise from improved adaptations to the conditions met in the environment during the sampling process. Although such studies reported the characterization of metagenome-derived enzymes, insights into their physiological aspect are often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this include the reluctance of many microorganisms present in these samples to lyse by protocols that have been developed mainly for DNA extraction from mesophilic samples and the release of very stable nucleases upon cell lysis. Nevertheless, significant progress has been made, and various methods allowing the isolation of highquality DNA from a variety of environments, i.e., soil (45,87,134,139), marine picoplankton (117), contaminated subsurface sediments (1), groundwater (128), hot springs and mud holes in solfataric fields (94), surface water from rivers (145), glacier ice (109), Antarctic desert soil (48), and buffalo rumens (25), have been developed.…”
mentioning
confidence: 99%